FORESIGHT FOR DEVELOPMENT OF EDUCATION TO MEDIUM- AND LONG-TERM PERSPECTIVE - Kuzmenko, Olha M. (Educological discourse, 2014)
The article is devoted to the foresight as one of the most progressive methodology of forecasting; the main methods of the foresight are distinguished; the main steps of the realization of the foresight-project are defined; it is analyzed the role of this methodology in the context of the forming of the new research approaches that based on the integration of knowledge, dialogue of the ideas, conceptions and paradigms.